Watersiporidae (Bryozoa) in Iberian waters: an update on alien and native species - Reverter-Gil, O.; Souto, J. (Marine Biodiversity, 2019)
Species of the genus Watersipora comprise an important invasive fouling group but are difficult to identify up to species level. This problem, in conjunction with the recent re-description of several member species, requires the revision of previous records and newly collected material in order to more precisely determine their actual presence and distribution. Here, we revise the identity and distribution of alien and native species of Watersiporidae in Iberian waters based on newly collected material, historical collections, and bibliographic data. Four species of Watersipora are now known from here. Watersipora cucullata is the only native species, present in the Spanish Mediterranean. Watersipora subatra seems to have been introduced relatively recently in Iberian and European Atlantic waters and has been expanding to other Atlantic localities. Watersipora arcuata was collected for the first time in Europe at the SW Spanish Atlantic coast in 1990 and recently in Mediterranean marinas. Watersipora souleorum is known in Iberian waters from two localities in the Gulf of Cadiz and in Gibraltar. With the recent redescription of the genus Watersipora, W. complanata is no longer a member. A new watersiporid genus, Terwasipora gen. nov., is described for this species. In Iberian waters, T. complanata comb. nov. is considered a native species, frequent and abundant in shallow waters along the Atlantic coast.